2009
DOI: 10.1002/14651858.mr000006.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Publication bias in clinical trials due to statistical significance or direction of trial results

Abstract: References to studies excluded from this review Chan 2004A {published data only} Chan AW, Hrobjartsson A, Haahr MT, Gotzsche PC, Altman DG. Empirical evidence for selective reporting of outcomes in randomized trials: comparison of protocols to published articles.. JAMA 2004;291:2457-65. Hrobjartsson A, Chan AW, Haahr MT, Gotzsche PC, Altman DG. Selective reporting of positive outcomes in randomised trials-secondary publication. A comparison of protocols with published reports. Ugeskrift for Laeger 2005; 167:31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
520
0
23

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 667 publications
(556 citation statements)
references
References 38 publications
13
520
0
23
Order By: Relevance
“…Language of publication(s). 367 (88) 25 (6) 27 (6) 259 (62) Single-centre study 159 (38) 1 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) 129 (81) 16 (10) 14 (9) 158 (99) Multi-centre study 260 (62) 1 238 (92) 9 (3) 13 (5) 101 ( perceived as an overestimation of the publication proportion. We excluded conference abstracts and other so-called 'grey literature' because those publications are often not indexed in electronic databases (in particular, abstracts of smaller conferences).…”
Section: Discussionmentioning
confidence: 99%
“…Language of publication(s). 367 (88) 25 (6) 27 (6) 259 (62) Single-centre study 159 (38) 1 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) 129 (81) 16 (10) 14 (9) 158 (99) Multi-centre study 260 (62) 1 238 (92) 9 (3) 13 (5) 101 ( perceived as an overestimation of the publication proportion. We excluded conference abstracts and other so-called 'grey literature' because those publications are often not indexed in electronic databases (in particular, abstracts of smaller conferences).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may have been affected by publication bias if studies finding null results were not published and therefore were not captured in this review. 51 …”
Section: Limitationsmentioning
confidence: 99%
“…• Publication or dissemination bias-Several systematic reviews of empirical studies have found that clinical trials with statistically significant (P<0.05) or positive results are more likely to be published than those with non-significant or negative results (39)(40)(41). Investigators' decisions not to submit papers with negative results for publication, rather than editors' rejection of such papers, tend to be the main source of publication bias (42).…”
mentioning
confidence: 99%